Spine deformation caused by inadequate posture adopted in front of a portable technological device - Aragón-Han, D.; Rodríguez-León, I. G.; Orozco-Villaseñor, D. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2017)
Body posture refers to the composition of the positions of all joints of the human body at a particular point in time. The interest in its analysis is due to the increase in the number of people that suffers back pain and proliferation of muscle skeletal problems such as dorsal kyphosis, lumbar lordosis, scoliosis or cifolordosis. These diseases have been associated with repetition and maintenance of certain postures that cause degenerative changes in articular tissues responsible for stabilizing the spine [11]. This paper uses image processing techniques in order to obtain biomedical analysis of posture in today’s society who do not care about postural hygiene and ergonomics when they are using either a computer, cell phone tablets or any technological device.